Studying poetry - Matterson, Stephen; Jones, Darryl, 1967- (London : Arnold, 2000)
This guide helps readers to understand and appreciate poetry as a genre, to develop an informed and articulate response to individual poems, and to become aware of the larger concerns involved in reading poetry. The first part of the book, "Form and Meaning," deals with the formal characteristics of poetry, such as metaphor, symbol, image, meter, rhythm, and rhyme. The second section, "Critical Approaches," explores the relationship between reading poetry and key concepts in critical theory, focusing on the poem as an object, the idea of the author, and the role of the reader. In part three, "Interpreting Poetry," the discussion explores such issues as political poetry, the poem in history, and the limits of poetry. This book refers to a wide range of poetry and poets and offers stimulating readings of individual poems.
TOC
Includes bibliographical references (p. [168]-169) and index.
English
Rokon Mahamud
Keywords: English poetry -- History and criticism; English poetry -- Study and teaching